Estrogen attenuates glutamate-induced cell death by inhibiting Ca(2+) influx through L-type voltage-gated Ca(2+) channels - Sribnick, Eric A. (2009)
Estrogen-mediated neuroprotection is observed in neurodegenerative disease and neurotrauama models; however, determining a mechanism for these effects has been difficult. We propose that estrogen may limit cell death in the nervous system tissue by inhibiting increases in intracellular free Ca(2+). Here, we present data using VSC 4.1 cell line, a ventral spinal motoneuron and neuroblastoma hybrid cell line. Treatment with 1 mM glutamate for 24 h induced apoptosis. When cells were pre-treated with 100 nM 17β-estradiol (estrogen) for 1 h and then co-treated with glutamate, apoptotic death was significantly attenuated. Estrogen also prevented glutamate-mediated changes in resting membrane potential and membrane capacitance. Treatment with either 17α-estradiol or cell impermeable estrogen did not mimic the findings seen with estrogen. Glutamate treatment significantly increased both intracellular free Ca(2+) and the activities of downstream proteases such as calpain and caspase-3. Estrogen attenuated both the increases in intracellular free Ca(2+) and protease activities. In order to determine the pathway responsible for estrogen-mediated inhibition of these increases in intracellular free Ca(2+), cells were treated with several Ca(2+) entry inhibitors, but only the L-type Ca(2+) channel blocker nifedipine demonstrated cytoprotective effects comparable to estrogen. To expand these findings, cells were treated with the L-type Ca(2+) channel agonist FPL 64176, which increased both cell death and intracellular free Ca(2+), and estrogen inhibited both effects. From these observations, we conclude that estrogen limits glutamate-induced cell death in VSC 4.1 cells through effects on L-type Ca(2+) channels, inhibiting Ca(2+) influx as well as activation of the pro-apoptotic proteases calpain and caspase-3.